The forint interest rate swap market and the main drivers of swap spreads - Csaba Csávás; Lóránt Varga; Csaba Balogh (Magyar Nemzeti Bank, 2008)
In our paper we present the most important characteristics of the forint interest rate swap market, as well as examine the determinants and the information content of the forint interest rate swap spreads. The turnover of the forint interest rate swap market has grown dynamically in recent years, and now it may reach, or even exceed, the turnover of the government bond market. Due to the hedging activity of interest rate swap market makers, there is a close linkage between the forint interest rate swap market and the government bond market. In terms of investors, the interest rate swap and government bond markets are strongly segmented. Consequently, the spillover from one market segment to the other is not perfect. Our analyses suggest that long-term forint interest rate swap spreads are exposed to the common impact of several factors. The strongest effects are attributed to government bond purchases by residents, the Maggie A spread, the slope of the yield curve and the forint/euro forward yield spread. In the developments of swap spreads, the impact of those trading strategies employing interest rate swaps can be detected. These are widespread in the domestic market, as is confirmed by anecdotal information. The results indicate that in certain cases the swap yields, while at other times the government bond yields carry additional information about long-term yield expectations. The values of the 5-year HUF/EUR forward spread 5 years ahead calculated from the swap yields and from the treasury yields differ markedly, and this difference is driven practically by the same factors that influence the interest rate swap spreads.
Keywords: G12; G14; G15; 330; forint interest rate swap market; government securities market; interest rate swap spread; swap spread model; Zinsderivat; Marktliquidität; Öffentliche Anleihe; Ungarn